Characterisation of traditional mango (mangifera indica L.) varieties of southern Kerala - Simi S (Department of Pomology and Floriculture, College of Agriculture, 2006)
Attempts were made at the Department of Pomology and Floriculture and the Department of Plant Biotechnology, College of Agriculture, Vellayani during June 2003 to December 2005 for characterizing the traditional mango (Mangifera indica L.) varieties of southern Kerala. Field visits were made in order to locate the varieties, to conduct survey and to collect the research materials. Fifty varieties were located in the four districts of southern Kerala, Trivandrum (17), Kollam (10), Pathanamthitta (6) and Alappuzha (17). Wide variability could be observed in the vegetative characters. The varieties / accessions varied remarkably in the vegetative characters like tree height, tree habit, leaf shape, leaf margin and leaf tip. Leaf length, leaf width and petiole length varied significantly between the varieties. The varieties / accessions varied widely with respect to the floral characters like position of inflorescence, shape, length, colour and density of flowers and season and regularity of flowering. The percentage of hermaphrodite flowers ranged from 8.4 (Velutha Muvandan) to 96.0 (Eara Local). The fruit characters like shape, presence of basal cavity, beak type, sinus type, presence of groove, type and slope of shoulders and apex exhibited by the varieties / accessions showed remarkable variation. High variability in fruit length, breadth, thickness, weight and volume could also be observed among the varieties / accessions. Muthalamookan recorded the highest length, breadth, thickness, weight and volume of fruits and Puliyan manga recorded the lowest values. Fruit weight ranged from 37.5 g to 826.0 g. Skin characters like colour, thickness, texture and weight also showed high variability. Percentage contribution of skin weight to the fruit weight varied from 8.4 (Ambalathara Local) to 37.7 (Puliyan). The different varieties varied considerably in the various flesh characters like weight, texture, adherence of skin to pulp, fibre content and colour. Pulp weight ranged from 14.8 g to 676.0g. Stone characters showed wide variation among the accessions. Quality characters of fruits varied widely among the accessions. Titrable acidity ranged from 0.12 per cent (Nedungolan) to 4.03 per cent (Eara Local). Ascorbic acid content ranged from 3.08 (Neendakara manga) to 119.05 (Natumav Type-2) mg / 100g. The total carotenoid content varied from 0.21 (Natumav Type-4) to 7.97 mg / 100g (Karpoora Varikka). The TSS of ripe fruits ranged from 8.77 to 25.71 0 Brix. Total sugar content ranged from 2.0 (Natumav Type-4) to 22.2 per cent (Neenda Karpooram). The reducing sugar content ranged from 0.9 per cent (Kalluketty) to 6.1 per cent (Perakka manga). Non- reducing sugar content varied from 0.81 per cent (Natumav Type-4)to 16.8 (Neenda Karpooram ). The crude fibre content in fruit pulp ranged from 0.4 per cent (Nedungolan) to 2.92 per cent (Natumav Type-3). Perakka manga was rated as the best in organoleptic evaluation. The accessions, Pulichi, Natumav Type- 2, Natumav Type-5, Kalluketty, Vellari Type-1and Kalkanda Vellari can be recommended as outstanding in pickling qualities. Of the table types, Nedungolan, Perakka manga, Muthalamookkan, Vellari Type-2, Karpooram manga and Neenda Karpooram can be recommended as superior with respect to important economic characters like fruit weight, pulp content and eating quality. Among the dual types, Kotookonam Varikka, Velutha Muvandan, Karpoora Varikka, Ambalathara Local and Kizhakkan Thali can be recommended as excellent in overall acceptability. DNA was extracted from young leaves using CTAB method (Dellaporta et al., 1983) with slight modification (Anuj et al., 2004). A total of 157 RAPDs (average of 3.74 bands per primer) were generated on PCR amplification using 42 decamer primers, of which 96.18 per cent (151 bands) were polymorphic. This accounts to an average of 3.6 bands per primer. Of these, ten primers yielded 92 scorable bands with an average of 9.2 bands per primer. The number of bands resolved per amplification varied from six to fourteen. A genetic similarity matrix was constructed using the Jaccard’s coefficient method. The pair wise similarity coefficient values ranged from 0.217 to 0.833. In the dendrogram, the thirty accessions subjected to RAPD analysis, were observed to group into seven clusters. The largest cluster contained 20 accessions. Four table varieties, Kappa manga, Mylapore manga, Neenda Karpooram and Kandiyoor Local were grouped together. All these were soft fleshed. Muthalamookan and Kolambi manga clustered together. Puliyan, Perakka manga, Kalluketty and Champa Varikka formed four separate clusters. Similarity assessment based on morphological and quality characters suggested that there was very high diversity among the traditional mango varieties. The pair wise similarity coefficient values varied between 0.042 and 0.708. The clustering pattern based on RAPD analysis was not strictly in accordance with that based on morphological and quality characters.